2019
DOI: 10.17557/tjfc.569363
|View full text |Cite
|
Sign up to set email alerts
|

FOLIAR APPLICATION OF SELENIUM, ZINC AND COPPER IN ALFALFA (Medicago sativa L.) BIOFORTIFICATION

Abstract: Biofortification of forage crops has an important role in improving the quality of plants used for animal nutrition. The field experiments were conducted in three consecutive years in Subotica, Serbia, in order to investigate the effect of Se, Zn, and Cu foliar fertilization on the yield, Se and Zn contents and nutrient efficiency, as well as on other mineral compositions of alfalfa hay. The treatments were as follows: i) control without fertilization, ii) 5 g Se ha-1 , iii) 10 g Se ha-1 , iv) 0.5 kg Zn ha-1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…This practice has been intensively studied in crops for human food, such as wheat, rice, or chickpea (Germ et al 2013;Ram et al 2016;Hla Hla et al 2019;Manojlović et al 2019), and to a lesser extent in grain crops for animal feeding (Rodrigo et al 2013;Novoselec et al 2018). The very few studies which have been conducted in forage crops deal mainly with alfalfa (Petković et al 2019). Among forage crops, legume species seems to be especially suitable for agronomic biofortification, since many studies have demonstrated a higher capacity to accumulate Se and Zn in their tissues (Poblaciones et al 2014;Poblaciones and Rengel 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This practice has been intensively studied in crops for human food, such as wheat, rice, or chickpea (Germ et al 2013;Ram et al 2016;Hla Hla et al 2019;Manojlović et al 2019), and to a lesser extent in grain crops for animal feeding (Rodrigo et al 2013;Novoselec et al 2018). The very few studies which have been conducted in forage crops deal mainly with alfalfa (Petković et al 2019). Among forage crops, legume species seems to be especially suitable for agronomic biofortification, since many studies have demonstrated a higher capacity to accumulate Se and Zn in their tissues (Poblaciones et al 2014;Poblaciones and Rengel 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of magnesium in alfalfa fodder varied, depending on the phenological phase at mowing, from 2.7 to 3.5 g kg -1 DM, similar to red clover fodder (2.1-3.8 g kg -1 DM) (Marković et al, 2007), which is consistent with our results. Hay obtained from alfalfa foliar fertilized with Se, Zn, and Cu during the vegetation had a P content of 2.2-2.4 g kg -1 DM, K 14.2 g kg -1 DM, Ca 2.36-3.46 g kg -1 DM, and Mg 2.7-3.2 g kg -1 DM (Petković et al, 2019). It was reported that N, K, and Ca were present in the highest concentration of alfalfa dry matter, while S, Mg, and P were present to a much lesser extent (Ferreira et al, 2015), which is in accordance with the results of our study.…”
Section: Resultsmentioning
confidence: 99%
“…found that NDF and ADF were not significantly affected by foliar application of Cu fertilizer. Petković et al 92 . found that no effect of Cu foliar application on CPC was observed.…”
Section: Improvement In Forage Quality Parameters With Zn and Cumentioning
confidence: 97%
“…Datt et al 125 found that NDF and ADF were not significantly affected by foliar application of Cu fertilizer. Petković et al 92 found that no effect of Cu foliar application on CPC was observed. Tripathi et al 126 observed increased CPC and decreased NDF and ADF levels in a sorghum crop due to the application of Cu along with other micronutrients.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 98%
See 1 more Smart Citation